Diseño de un plan deportivo para el adulto mayor con la aplicación de ejercicios aeróbicos y anaeróbicos alácticos utilizando pelota medicinal en el gimnasio “SILUET GYM” del cantón Rumiñahui en el año 2012. - Manosalvas Vegay, Jadira Alexandra (2013)
This research was an exploratory, descriptive and correlate about exercises elderly who have the need for their daily lives, active teaching strategies and techniques in physical activity of the elderly ofthe elderly Siluet Gym in the Rumiñahui Canton. For that reason was considered problematic situation regarding the lack of adequate and practical exercises for elderly attending the Siluet Gym in the Rumiñahui Canton, as it was found that the use of methods, strategies and techniques to practice exercises for elderly, determined that the practice of exercises suitable for age not require, remain traditional and non-professionals. The age is marked by a series of changes that all people have the morphological, functional and psychological. Many of these changes begin to occur when it reaches sexual maturity, which we call adulthood. From there the roles and physical abilities begin to decline slowly. Not only can we attribute our own body factors, but also the lifestyle and environment around us. Therefore, physical activity is presented as essential for improving lifestyle and those obtained by both prevention of decay of functions and physical abilities. But keep in mind the peculiarities of older people present when physical activity or sports physical training.